Inflation surprises and election outcomes - Jonathan-Julian Federle; Cathrin Mohr; Moritz Schularick (Kiel Institute for the World Economy (IfW Kiel), 2024)
We study the political consequences of inflation surprises, focusing on votes for extremist and populist parties in 365 elections in 18 advanced economies since 1948. Inflation surprises are regularly followed by a substantial increase in vote shares of extremist, anti-system, and populist parties. An inflation surprise of 10 percentage points leads to a 15% increase in their vote share, comparable to the increase typically seen after financial crises. We show that the change in voting behavior is particularly pronounced when real wages decline, and less evident when real wages are not affected. Our paper points to considerable political after-effects of unexpected inflation.
Keywords: D72; E31; N40; N10; 330; Inflation; Economic Voting; Extremism; Populism; Radicalization